2,4-dichlorophenoxyacetic acid (2,4-D) exposure during postnatal development alters the effects of western diet on mouse prostate - Rocha, V. A. [UNESP]; Aquino, A. M. [UNESP]; Magosso, N. [UNESP]; Souza, P. V. [UNESP]; Justulin, L. A. [UNESP]; Domeniconi, R. F. [UNESP]; Barbisan, L. F. [UNESP]; Romualdo, G. R. [UNESP]; Scarano, W. R. [UNESP] (Elsevier, 2023)
Western diet (WD), abundant in saturated fats and simple carbohydrates, has been associated with the development of prostate diseases. In addition, 2,4-dichlorophenoxyacetic acid (2,4-D), an herbicide used in agricultural and non-agricultural settings, may interfere with the endocrine system impacting reproductive health. The association of both factors is something common in everyday life, however, there are no relevant studies associating them as possible modulators of prostatic diseases. This study evaluated the action of the herbicide 2,4-D on the postnatal development of the prostate in mice fed with WD. Male C57Bl/6J mice received simultaneously a WD and 2,4-D at doses of 0.02, 2.0, or 20.0 mg/kg b.w./day for 6 months. The prolongated WD intake induced obesity and glucose intolerance, increasing body weight and fat. WD induced morphological changes and increased PCNA-positive epithelial cells in prostate. Additionally, the WD increased gene expression of AR, antioxidant targets, inflammation-related cytokines, cell repair and turnover, and targets related to methylation and miRNAs biosynthesis compared to the counterpart (basal diet). 2,4-D (0.02 and 2.0) changed prostate morphology and gene expression evoked by WD. In contrast, the WD group exposed to 20 mg/kg of 2,4-D reduced feed intake and body weight, and increased expression of androgen receptor and genes related to cell repair and DNA methylation compared to the negative control. Our results showed that 2,4-D was able to modulate the effects caused by WD, mainly at lower doses. However, further studies are needed to elucidate the mechanisms of 2,4-D on the obesogenic environment caused by the WD.
Keywords: 2; 4-D; Herbicides; Obesity; Prostate; Reproductive toxicology